Blockchain and its derived technologies shape the future generation of digital businesses: a focus on decentralized finance and the Metaverse - Banaeian Far, Saeed; Imani Rad, Azadeh; Rajabzadeh Asaar, Maryam (Data science and management, 2023)
Without a doubt, blockchain, as one of the most valuable technological advancements, has been introduced over the past decade and has played a significant role in the industrial revolution. The emergence of other technologies derived from blockchain, such as decentralized finance (DeFi) and the Metaverse, has fundamentally transformed people’s daily lives and profoundly impacted future versions of digital businesses. This study explored the evolution of digital businesses in the near future, with a specific focus on the two primary technologies mentioned above. First, we reviewed DeFi-based technologies, including GameFi, SciFi, SocialFi, and others which serve as foundational building blocks for future jobs and businesses. Second, we examined Metaverse-based jobs, such as Metaverse-based academies and markets which are expected to be launched as commonly used businesses. Ultimately, this study provides several guidelines, such as how to use DeFi 2.0 and apply centralized decentralized finance (CeDeFi)-based platforms. Additionally, it offers future directions for launching these businesses, including controlling the progress of artificial intelligence (AI) in practical applications, utilizing cloud-assisted models for the Metaverse, and providing conditional privacy for future Metaverse-based businesses.